2017
DOI: 10.1002/ajp.22644
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of habitat loss and fragmentation on the activity budget, ranging ecology and habitat use of Bale monkeys (Chlorocebus djamdjamensis) in the southern Ethiopian Highlands

Abstract: Understanding the extent to which primates in forest fragments can adjust behaviorally and ecologically to changes caused by deforestation is essential to designing conservation management plans. During a 12-month period, we studied the effects of habitat loss and degradation on the Ethiopian endemic, bamboo specialist, Bale monkey (Chlorocebus djamdjamensis) by comparing its habitat quality, activity budget, ranging ecology and habitat use in continuous forest and two fragments. We found that habitat loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(117 citation statements)
references
References 58 publications
0
115
0
2
Order By: Relevance
“…), activity budget and ranging ecology (Mekonnen et al. ), and genetic variability (Mbora & McPeek ; Ruiz‐Lopez et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), activity budget and ranging ecology (Mekonnen et al. ), and genetic variability (Mbora & McPeek ; Ruiz‐Lopez et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in view of the critical functional roles arboreal primates have in tropical rainforests (Estrada et al 2017). Shared patterns in population density may translate into similar effects due to habitat fragmentation and human disturbance on overall population size and demography (de Almeida-Rocha et al 2017), activity budget and ranging ecology (Mekonnen et al 2017), and genetic variability (Mbora & McPeek 2015;Ruiz-Lopez et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Instead the effect of leaf consumption on time budget trade-off was modulated by fragment quality. Previous research has indicated that anthropogenic habitat disturbance could impact primate time budgets in a variety of ways [Palma et al, 2011;Ordóñez-Gómez et al, 2016;Mekonnen et al, 2017], but our study is possibly the first to provide evidence of a link between leaf consumption and variation in energy budget strategies depending on habitat quality: from a lowinvestment/low-return strategy in high-quality fragments to a high-investment/low- return budget in low-quality fragments. Such variation could imply less net energy available under a more folivorous diet, as leaves, although rich in proteins and minerals [Ganzhorn et al, 2017], tend to have lower energy content than fruits, and howler monkeys would obtain less energy [Silver et al, 2000].…”
Section: Discussionmentioning
confidence: 79%
“…Habitat fragmentation causes increasing length of boundary, reduces size of patches and respectively halts normal functioning of ecological processes (Collinge 1996). This habitat fragmentation was posing chronic challenge for endemic animals' viability and conservation activities especially at fragmented landscapes (Mekonnen et al 2012;Mamo and Bekele 2011;Temesgen 2015;Mekonnen et al 2017). This is because animals in a fragmented ecosystem migrate from patches to patches in search of feed and water.…”
Section: Discussionmentioning
confidence: 99%